PENGARUH OPTIMALISASI KOMUNIKASI KESEHATAN PADA PUSAT PELAYANAN KESEHATAN DASAR TERHADAP PENINGKATAN DERAJAT KESEHATAN ANAK USIA DINI - Susanne Dida (Indonesian Journal of Dialectics, 2011)
This study emphasizes on influence of optimalization in health communication at the basic health center on the level of children’s wellbeing  . The training is given by Department of Health that referred to Standard of Minimum Services for health provider at Basic Health center in province and district. By 17 programs of Standard of minimum services and standard of Operational Procedure,  gradually the skill of health provider will increase and finally will influence to scale up the level of wellbeing of children.        The implementation of health service procedure needs a right strategy of communication in essential, such as  if the patient adherence in clinicians we can  help to identify the causes of their diseases. So the knowledge and skill in communication and life experience of provider as well as their ever changing cognitive, treatment, believe, and determine the degree of recovery. Then we found the theorizing and research concerning the patient- provider interaction and children serve more specific in a model of bio-psychosocial.          The research design is the quasi-experiment by using the control group which is purpose to test some research propositions.         The hypothesis, the trained provider has a greater knowledge and skill in implementation the standard of minimum procedure compared with untrained provider in a control area, so the level of wellbeing of children in intervention area more increasing.                         The result of the testing shows the level of wellbeing of children, fixing by the way to service, conferral medicine, a quality of communications between patient-health provider.In summary, research has demonstrated that the key elements of patient-health provider communication influencing satisfaction include a caring and understanding manner on the part of health care provider, medical competence, balance inquiry into psychological and bio-medical concern, continuity of patient – health provider relationship and the expression of patient expectation. These finding have implication for both training and clinical practice and these implementation are elaborate to the level of wellbeing of children.